HUBUNGAN STATUS MEROKOK DENGAN KUALITAS HIDUP DI KOTA YOGYAKARTA - , SUCI SINTIA PERDANA, Susi Ari Kristina, M.Kes., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Cigarettes as a product that does not have health benefits, should not be consumed by the public as much impact caused both to themselves and the environment. One of them is a decrease in quality of life due to smoking. This study aims to examine the relationship of smoking status with quality of life and the relationship of smoking behavior with the quality of life in the city of Yogyakarta. This research is a cross-sectional survey in four sub-district of Yogyakarta is Pakualaman, Danurejan, Gondokusuman, and Gedongtengen using WHOQOL-BREF instrument made and translated into Indonesian by the WHOQOL group. Sampling was done by a non-random (nonrandom sampling) with a convenience sampling technique. 142 samples were obtained and analyzed using the SPSS 15. Independent samples t-test was used for analysis of the association of smoking status with quality of life, while ANOVA for analysis of the relationship of smoking behavior with the quality of life. The results indicate a higher quality of life compared to non-smokers smokers in all domains of quality of life and in general showed a significant relationship (physical domain (p = 0.004), psychological (p = 0.005), the environment (p = 0.002) and total domain scores (p = 0.006)). Judging from the behavior of smoke, light smokers had a better quality of life compared to moderate and heavy smokers. Heavy smokers have the lowest value in the physical domain and the environment than the mild and moderate smokers. Judging from the relationship, smoking behavior showed no significant relationship with quality of life (physical domain (p = 0.963), psychological (p = 0.873), social relationships (p = 0.531), the environment (p = 0.788) and total domain scores (p = 0.800)).